Transient High-Frequency Electromagnetic Force Calculation for Linear Induction Motors Under Pulse Width Modulation Current Excitation - Mingke Li; Jin Xu; Junjie Zhu; Yuhu Wang; Tairan Chen (Machines)
Because of their transient working mode and end effects, it is particularly difficult to compute high-frequency electromagnetic forces on linear induction motors under PWM current simulation. The current methods for computing high-frequency electromagnetic forces in transient operating conditions are computationally expensive and have limited practicality. To deal with these issues, this paper introduces a non-periodic transient high-frequency electromagnetic force calculation model. Firstly, an examination of a linear induction motor under PWM currents demonstrates that the transient magnetic field calculation issue in a linear induction motor can be simplified to a periodic boundary steady-state magnetic field calculation problem. Based on this, a 2D magnetic field analytical model is established for high-frequency magnetic field calculation. Subsequently, a hybrid approach employing both finite element analysis and analytical methods is employed to compute the transient magnetic field. Finally, electromagnetic forces are calculated across the entire frequency spectrum, and the correctness of the model is validated indirectly through motor vibration experiments. This model offers faster and more accurate results than finite element analysis, making it suitable for application in the iterative stages of motor optimization design and applicable to rotary induction motors.